2018
DOI: 10.29252/jafm.11.01.28235
|View full text |Cite
|
Sign up to set email alerts
|

On the Instability of Two Dimensional Backward-Facing Step Flow using Energy Gradient Method

Abstract: In the present paper, the energy gradient method is implemented to study the instability of 2-D laminar backward-facing step (BFS) flow under different Reynolds numbers and expansion ratios. For this purpose, six different Reynolds numbers (50 ≤ Re ≤ 1000) and two various expansion ratios of 1.9423 and 3 are considered. We compared our results of the present study with existing experimental and numerical data and good agreement is achieved. To study of fluid flow instability, we evaluated the distributions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
6
0
3
Order By: Relevance
“…A Figura 1 mostra o domínio geométrico que é objeto de estudo deste trabalho. Tal geometria é conhecida como Duto com Ressalto (ou no inglês, Backward-Facing Step (BFS)), onde os parâmetros mostrados na figura, com suas proporções, foram tomados de acordo com Nowruzi et al [9]. As equações do escoamento são dadas pelo conjunto das equações de Navier-Stokes incompressíveis, que são as equações da continuidade e do momento,…”
Section: Modelagem Matemáticaunclassified
See 1 more Smart Citation
“…A Figura 1 mostra o domínio geométrico que é objeto de estudo deste trabalho. Tal geometria é conhecida como Duto com Ressalto (ou no inglês, Backward-Facing Step (BFS)), onde os parâmetros mostrados na figura, com suas proporções, foram tomados de acordo com Nowruzi et al [9]. As equações do escoamento são dadas pelo conjunto das equações de Navier-Stokes incompressíveis, que são as equações da continuidade e do momento,…”
Section: Modelagem Matemáticaunclassified
“…Os valores obtidos neste trabalho para o comprimento da zona de recirculação são comparados na Tabela 1 com resultados obtidos na literatura [5,6,9], todos efetuados para raio de expansão ER = 1, 9423.…”
unclassified
“…BFS reattachment length growing with Re is stated that as not linear as symmetrical sudden expansion. Nowruzi et al [9] used energy gradient method for simulating BFS laminar flow. Authors provide an excellent literature survey, and the flow related part are very important in respect of the present paper.…”
Section: Introductionmentioning
confidence: 99%
“…He proposed that the dimensionless parameter in energy gradient method especially the energy profiles could provide a satisfactory prediction for the transition. Nowruzi et al (2018) investigated the flow instability of a backward facing step flow with the energy gradient method, and valuated the local velocity, vorticity as well as the energy gradient function. Zheng et al (2016Zheng et al ( , 2018 investigated the blade-tongue interaction and found that this interaction intensified the local pressure fluctuation which further intensified the local flow stability.…”
Section: Introductionmentioning
confidence: 99%